-7n(4n+5)=0

Simple and best practice solution for -7n(4n+5)=0 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -7n(4n+5)=0 equation:



-7n(4n+5)=0
We multiply parentheses
-28n^2-35n=0
a = -28; b = -35; c = 0;
Δ = b2-4ac
Δ = -352-4·(-28)·0
Δ = 1225
The delta value is higher than zero, so the equation has two solutions
We use following formulas to calculate our solutions:
$n_{1}=\frac{-b-\sqrt{\Delta}}{2a}$
$n_{2}=\frac{-b+\sqrt{\Delta}}{2a}$

$\sqrt{\Delta}=\sqrt{1225}=35$
$n_{1}=\frac{-b-\sqrt{\Delta}}{2a}=\frac{-(-35)-35}{2*-28}=\frac{0}{-56} =0 $
$n_{2}=\frac{-b+\sqrt{\Delta}}{2a}=\frac{-(-35)+35}{2*-28}=\frac{70}{-56} =-1+1/4 $

See similar equations:

| 31958x^2+(362x^2)=123 | | y=6*4^-3 | | x^2=(8/12) | | 100=1x+5 | | x+3×4=10 | | 6(x-5)=5(x-40) | | 6(x-5)=5(x-40 | | 234x^2+(546x^2)-(352x^2)+(1234x^2)-(8x^2)+(2354x^2)+(5555x^2)=17 | | -36-(1+7x)=6(-7-x) | | y=5(-5)-2 | | 113-y=157 | | 234x^2+(546x^2)-(352x^2)+(1234x^2)*(8x^2)+(2354x^2)+(5555x^2)=16 | | 2x=2(x-6) | | 4/5x30=3- | | 234x^2+(546x^2)-(352x^2)+(1234x^2)-(8x^2)+(2354x^2)=13 | | 234x^2+(546x^2)-(352x^2)+(1234x^2)*(8x^2)+(2354x^2)=13 | | 3d-3)=d-3 | | 4(x-1)+7x=2x+4 | | 234x^2+(546x^2)-(352x^2)+(1234x^2)*(8x^2)+(2354x^2)*(124326x^2)=13 | | 9.52+x=17.88 | | x+8/x=12/9 | | (n-9)*10=80 | | 1.2*^10^-5=2x(x) | | 5x=103 | | 6x+5=3+14 | | 6(x+1)+48=90 | | 1.2x10^-5=2x(x) | | -25=6x-7 | | 2x/(x+3)=1 | | 3=3.3x​ | | d-13= 25 | | y=5(-1/2)-2 |

Equations solver categories